THE ROLE OF INNOVATIVE COMPUTER TECHNOLOGIES FOR THE IMPROVEMENT AND FORMATION OF STUDENTS’ SPEAKING SKILLS AT ENGLISH LESSONS - Zulfizar Karimova (International Journal of Innovative Technologies in Social Science, 2020)
The issues of teaching a foreign language using computer technology are considered in this article. Moreover, the article gives the concept of such a term as the communicative activity of students, that is, practical knowledge of speaking skills in a foreign language; lists the tasks of the teacher, whose role is to enhance the speech activity of each student in the educational process, creating a situation for their creative activity. The article provides evidence that the use of computer technologies in the classroom makes it possible to move from reproductive forms of educational activity to independent, creative types of work, where the emphasis is on the formation of students’ communicative culture and the development of skills in working with various types of information and its sources.